Clinical Holistic Medicine: Chronic Infections and Autoimmune Diseases - Søren Ventegodt; Joav Merrick (The Scientific World Journal)
The consciousness-based (holistic) medical toolbox might be useful in general practice and in cases of recurrent infections and chronic infection or inflammation. From our clinical experiences, there is hope for improvement from a number of diseases caused by disorders affecting the regulation of the immune system when the physician includes the holistic medical approach.Our scientific understanding of the connection between consciousness and cellular order is still limited. Consciousness-based holistic medicine removes (as explained by the holistic process theory of healing) the “blockages” in the tissues of the body and facilitates function and informational exchange of the cells of the body. Many blockages and repressed feelings in an area would imply “noise and disturbances” on the level of intercellular communications, which in turn means major difficulties for the cells of the immune system. For this they are totally dependent on the body information system, which the holistic treatment aims to recover. Processing the blockages increases the coherence of the cells and organism, thus increasing the intercellular flow of information in the area and thus strengthening the immune defense and healing the disease. The area of clinical holistic medicine is going through a rapid development and the toolbox of consciousness-based medicine is available for dealing with many diseases arising from disturbances in the regulation of the immune system. Holistic medicine has yet to be better explained scientifically and our proposed holistic cures have yet to be documented clinically. We invite the medical community to cooperate on this important challenge.